Digital performance assessment for agroecological transitions in rice: Evidence from Vietnam - Nelson, Katherine (International Rice Research Institute, 2024)
As Vietnam advances its Green Growth Strategy and the National Action Plan on Transparent, Accountable, and Sustainable Food Systems, digital innovations play a pivotal role in promoting sustainable, low-emission agricultural practices. Key tools discussed include RiceMoRe, a government-led statistical reporting system; WaterIntel, an SMS-based field water level monitoring tool; and FarMoRe, a performance assessment app designed to benchmark sustainability practices under the "1 Must Do, 5 Reductions" (1M5R) framework. Developed through an iterative co-design process with farmers and field agents, these tools enhance data-driven decision-making by providing real-time insights into resource management, greenhouse gas emissions, and sustainability performance. They improve efficiency, traceability, and inclusivity, particularly by supporting farmers with diverse levels of digital literacy. Furthermore, the integration of social benchmarking, tailored advisories, and potential linkages to high-value markets demonstrates the transformative potential of digital tools in driving agroecological transitions and fostering resilient, low-emission rice production systems in Vietnam.